Integration of Personal Safety in Students Training on the Specialty “Civil Safety” at Technical Institutions of Higher Education - Nataliіa Yevtushenko; Natalia Tverdokhliebova (Educational Challenges, 2024)
Security is considered a legitimate goal of every society. In recent years of the pandemic and then the war in Ukraine, the issue of the security paradigm has become particularly relevant. It prompts a revision of conceptual approaches to the formation of human personal security competencies and especially the mechanisms and ways of ensuring it in society and the state in the present conditions. Therefore, in theory, national and international security concepts are being developed, and more recently, individual, social, and global security. This indicates, among other things, a significant expansion of new dimensions of security when political independence, territorial integrity, and viability of the country, as well as the survival and development of its inhabitants, are at stake. Security in itself should have the status of a fundamental human right.